Influence of the Workload and Years of Experience of Nurses on Hemodialysis Quality Using Korean National Hemodialysis Adequacy Evaluation Data. (10th March 2022) - Kim, Yunmi; Lee, Kyounga
The aim of this study is to examine the influence of nurses' workload and years of experience on the rate of patients with normal calcium–phosphorus products levels and the adequacy evaluation grade of hemodialysis (HD) facilities using 2015 and 2018 national HD adequacy evaluation data. The data of 616 hospital-level outpatient HD facilities were analyzed using multiple linear regression and ordinal logistic regression. A higher rate of nurses with ≥2 years of HD experience was correlated with a higher rate of patients with normal calcium–phosphorus levels. As the average daily number of HD cases per nurse increased, the probability of HD facilities' receiving the higher adequacy evaluation grade decreased by 83% (odds ratio (OR)=.17, 95% confidence interval (CI)=.14–.22), whereas it increased by 4% as the rate of nurses with ≥2 years of HD experience increased by 1%p (OR=1.04, 95% CI=1.03–1.05). Reducing the nursing workload by maintaining sufficient nurses and increasing the rate of nurses with ≥2 years of HD experience would improve the quality of HD and patient outcomes.